Ethnic enterprise and generational change: Indian-owned small and medium enterprises in Malaysia / Jesrina Ann Xavier - Jesrina Ann, Xavier (2017)
Theoretical perspectives regularly employed to analyse the growth of enterprises owned by members of ethnic groups appear increasingly inapplicable. These theories can no longer be considered applicable, especially in Malaysia, where ethnic-based enterprises established by the first generation, has now been passed on to the second or third generation. To provide a greater understanding of the evolution of Malaysian Indian businesses, a variety of possible explanations was examined. This includes an investigation on the changes in class and ethnic resources, the shift in market conditions and state policies as well as the transformation in networks. This thesis pays particular attention to how an ethnic enterprise functions, in terms of types of goods and services produced and its targeted market, after a new generation of owners emerges. An overall qualitative research methodology through a phenomenological approach was employed towards this end. Due to the nature of this thesis which tracks the generational change of Indian businesses in Malaysia, the case study method was applied to eleven enterprises. The primary data collection method was an analysis of the annual company reports followed by interviews with the founders as well as the second or third generation owners of these businesses. The theoretical and empirical evidence from this study provides key insights into the applicability of the concept of ethnic enterprise in Malaysia following a generational transition.